Planning of Facilities and Infrastructure in Islamic Education - Melda Diana Nasution (Yayasan Marwah Madani Riau, 2021)
This paper describes the management of facilities and infrastructure in Islamic educational institutions. This discourse is important to describe because the education system is an interrelated component such as curriculum, materials, methods, educators, students, facilities, tools, approaches and so on. So far, the understanding of the concept of integration and interconnection between the sub-systems above is still lacking so that the learning process is not optimal. This study uses a library research method with an analytical-descriptive approach. The results of the study indicate that the management of educational facilities and infrastructure is a collaborative process for the effective use of all educational facilities and infrastructure. The purpose of managing school facilities and infrastructure is to provide professional services so that the learning process can take place effectively and efficiently. The management process of Islamic education facilities and infrastructure includes (1) Planning of Islamic education facilities and infrastructure (2) Procurement of Islamic education facilities and infrastructure (3) Inventory of Islamic education facilities and infrastructure (4) Supervision and maintenance of Islamic education facilities and infrastructure (5) Elimination school facilities and infrastructure. The conclusion of this study is that the management of facilities and infrastructure in Islamic educational institutions must be oriented to the principles of being on time, on target and effective.